Determination of rural economic concentration areas (RECAs) through spatial analysis for designing the Colombian economic census framework - García Vélez , Gustavo Adolfo; Durán Gil , Carlos Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Thirty years have passed since the only economic census in Colombia. Therefore, it is necessary to have a statistical framework that guarantees the inclusion of the economic units of the country to develop a new census. Considering that the rural areas have specific characteristics regarding localization and proximity of the economic activity, which can affect the costs and time of the census, a methodology with an exploratory and descriptive scope was proposed. It is supported by the use of diverse sources and the application of spatial analysis techniques based onthe localization, proximity, and concentration of the economic units with the aim of determining the rural economic concentration areas (RECAs). As a result, 5,537 RECAs were identified, and they are located in 80% of the second-level territorial divisions, with a central tendency in their median of five establishments and a surface area of 15.6 hectares. Although there are no similarreferences of this type, the determination of these areas was based on obtaining thematic and geographic consistency from the sources used and the configuration of spatial concentrations.However, being an exploratory method, it is open to continuous improvement and feedback, seeking to be a reference in the conformation of statistical frameworks.